Cytokines and chemokines skin gene expression in correlation with immune cells in blood and severity in equine insect bite hypersensitivity - Jebbawi, Fadi; Chemnitzer, Alex; Dietrich, Macsmeila; Pantelyushin, Stanislav; Lam, Juwela; Rhiner, Tanya; Keller, Giulia; Waldern, Nina; Canonica, Fabia; Fettelschoss-Gabriel, Antonia (Frontiers in Immunology, 2024)
Background Insect bite hypersensitivity (IBH) is the most frequent skin allergy of horses and is highly debilitating, especially in the chronic phase. IBH is caused by IgE-mediated hypersensitivity reactions to culicoides midge bites and an imbalanced immune response that reduces the welfare of affected horses. Objective In the present study, we investigated the pathological mechanisms of IBH, aiming to understand the immune cell modulation in acute allergic skin lesions of IBH horses with the goal of finding possible biomarkers for a diagnostic approach to monitor treatment success. Methods By qPCR, we quantified the gene expression of cytokines, chemokines, and immune receptors in skin punch biopsies of IBH with different severity levels and healthy horses simultaneously in tandem with the analysis of immune cell counts in the blood. Results Our data show an increase in blood eosinophils, monocytes, and basophils with a concomitant, significant increase in associated cytokine, chemokine, and immune cell receptor mRNA expression levels in the lesional skin of IBH horses. Moreover, IL-5Ra, CCR5, IFN-γ, and IL-31Ra were strongly associated with IBH severity, while IL-31 and IL-33 were rather associated with a milder form of IBH. In addition, our data show a strong correlation of basophil cell count in blood with IL-31Ra, IL-5, IL-5Ra, IFN-γ, HRH2, HRH4, CCR3, CCR5, IL-12b, IL-10, IL-1β, and CCL26 mRNA expression in skin punch biopsies of IBH horses. Conclusion In summary, several cytokines and chemokines have been found to be associated with disease severity, hence contributing to IBH pathology. These molecules can be used as potential biomarkers to monitor the onset and progression of the disease or even to evaluate and monitor the efficacy of new therapeutic treatments for IBH skin allergy. To our knowledge, this is the first study that investigated immune cells together with a large set of genes related to their biological function, including correlation to disease severity, in a large cohort of healthy and IBH horses.